HUBUNGAN SELF EFFICACY DAN DUKUNGAN PASANGAN DENGAN SELF CARE BEHAVIOUR PENDERITA DM TIPE II DI KLINIK KITAMURA - Wahyuni, Sri (Tanjungpura Journal of Nursing Practice and Education, 2021)
Background: Diabetes mellitus (DM) is a chronic disease that requires continuous self-care. Diabetes that is often not controlled can lead to complications and death. In increasing self-care behavior, there are several factors that influence, one of which is self-efficacy and spousal support.Method: This cross-sectional study involved 51 respondents, selected through a purposive sampling method. Instruments used include a set of questionnaires of Diabetes Management Self Efficacy (DMSE), Spousal Support, and Summary of Diabetes Self Care Activities (SDSCA). Spearman"™s test was used for statistical analysis.Result: Aged 56-60 years and 60 years (25.5%), female (66.7%), high school education (43.1%), housewives 49.0% and long suffered DM 1-5 years (60.8%). Based on the results of statistical tests, it was found that the level of self-efficacy was P value 0.000 (0.05) and partner support was P value 0.000 (0.05).Conclusion: There was an association between self-efficacy and spousal support with self-care behavior in people with type 2 diabetes mellitus.  Keywords: Spousal support, self-care behavior, self-efficacy